Digital Agricultural Innovation as a Response to the Challenges of the Modern Agricultural Sector in Arab Countries: The Experience of the United Arab Emirates - zoulikha massasoudi; Fatima Zahra Benseghier (Journal of Excellence for Economics and Management Research, 2024)
The aim of this study is to explore the challenges facing the Arab world and examine the technologies and methods of digital agricultural innovation applied to address them, by providing a descriptive and analytical framework of these difficulties in Arab countries and presenting the experience of the United Arab Emirates, which is a pioneer in implementing digital agricultural innovations. The importance of the study lies in considering digital agricultural innovation as an innovative solution to the current challenges facing this sector due to its contribution to improving productivity and achieving sustainability in Arab countries.   The study concluded that there is a significant commitment to adopting technology and innovation in agriculture, although some Arab countries still rely on traditional farming. Achieving digital agricultural innovation requires adopting comprehensive strategies aimed at enhancing the agricultural sector. It is viewed as a strong response to the numerous challenges facing the sector, making it a suitable solution for Arab countries suffering from food shortages. The United Arab Emirates has achieved satisfactory results in agricultural innovation, positioning itself as a leader in this field.